Strategies to Improve Teacher Ability in Using The Madrasah E-Learning Application During the COVID-19 Pandemic - Riyan Rizaldi, Dedi; Doyan, Aris; Fatimah, Ziadatul; Zaenudin, Muhamad; Zaini, Muhammad (Malikussaleh University, Aceh, Indonesia, 2021)
Learning during a pandemic requires every teacher to be able to improve literacy skills in terms of using technology to help the learning process. However, due to the rapid paradigm shift due to the COVID-19 pandemic, from direct learning to online-based learning. Therefore this activity was carried out to improve the ability of Madrasah Aliyah Plus Nurul Islam Sekarbela teachers in using various learning support applications, especially the Ministry of Religion E-learning. The Ministry of Religion E-learning application is an application recommended by the Ministry of Religion of the Republic of Indonesia for use in the distance learning process during the COVID-19 pandemic at the madrasa level. The use of applications in the learning process is expected to be able to increase student motivation and enthusiasm for learning during the learning period from home and still pay attention to health protocols. Participants in this activity were attended by all teachers who teach at Madrasah Aliyah Plus Nurul Islam with a total of 36 people. In its implementation, this activity consists of three stages, namely 1. The preparation stage, 2. Implementation stage, and 3. Evaluation stage with each activity an evaluation process is carried out to ensure that the initial objectives of this activity can be achieved. Based on the activities that have been carried out, it can be concluded that this mentoring activity is needed by teachers in understanding the use of the Ministry of Religion E-learning application with various supporting features and its implementation. Also, after carrying out this activity, teachers began to get used to the use of the Ministry of Religion's E-learning application in carrying out the learning process during the COVID-19 pandemic.